Bismuth-catalyzed and doped p-type ZnSe nanowires and their temperature-dependent charge transport properties. Issue 4 (7th January 2016) - Zhang, Xiwei; Jie, Jiansheng; Zhang, Xiujuan; Yu, Fengjun
Abstract : Simultaneous ZnSe nanowire growth and p-type doping is realized in one step by using Bi as the catalyst and dopant via chemical vapor deposition. Temperature-dependent electrical measurements are used for understanding the charge transport mechanism and the doping effect. Abstract : Au catalysts have been found to diffuse into semiconductor nanostructures and form non-radiative recombination centers during the synthesis process. This adverse impact is even more on the p-type doping of ZnSe nanostructures due to the self-compensation effect. Herein, low melt-point Bi was used as a catalyst for the synthesis of p-ZnSe nanowires via the VLS mechanism while the incorporation of Bi catalyst atoms causes effective p-type doping in the as-grown nanostructures. Top-gate MISFETs were fabricated to confirm the p-type conduction of Bi-catalyzed and doped ZnSeNWs. Temperature-dependent electrical measurements were used for understanding the charge transport mechanism and the doping effect of semiconductors. The thermal activation behavior of carriers is considered to dominate in the temperature range of 150–300 K while the 3D Mott VRH mechanism is considered to prevail over other mechanisms in the lower temperature range of 50–140 K.